ANALYSIS OF INNOVATION IN THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM TO FOSTER STUDENTS’ REFLECTIVE RELIGIOUS THINKING AT MTSN 1 SLEMAN - Aufa Fatchia Rahma; Muh. Wasith Achadi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
This research stems from the need to introduce innovation into the Islamic Religious Education curriculum, particularly to ensure its relevance to the demands of learning in the digital era and to foster students' reflective religious thinking skills. The primary focus of this study is to examine how the innovation in the Islamic Religious Education curriculum is implemented in the learning context at MTsN 1 Sleman. The approach used is qualitative and phenomenological, enabling researchers to understand firsthand experiences and practices. The research subjects included purposively selected Islamic Religious Education teachers and students. Data collection was conducted through in-depth interviews and documentation, followed by analysis through data reduction, presentation, and conclusion drawing. The research findings indicate that innovation in the Islamic Religious Education curriculum is achieved through more contextual and dialogical learning, supported by digital media and diverse methods. This pattern provides space for students not only to understand religious teachings but also to reflect on them and relate them to everyday life. From there, reflective religious thinking skills develop more deeply and are not merely a formality. However, in practice, several obstacles still arise, primarily due to limited technological resources and environmental influences.